Relapse of tuberculosis in rural areas of Bangladesh - Islam, Md Nazrul; Mahmud, Shah Noor; Ali, Ahmed; Afsana, Kaosar; Hashima-E-Nasreen; Islam, Md. Akramul; Chowdhury, AMR; Chowdhury, Sadia A (BRAC Research and Evaluation Division (RED), 2019)
The study conducted to investigate the relapse rate of TB in two thanas (KahaIoo and Furbari) of ' Women's Health and Development Programme (WlIDP) in August 1995. Of the 482 study cases, 435 (900A» treatment completed cases were interviewed, 4.7% died, 2.7% migrated and the rest did not response. The overall relapse rate was 4.10/0. Relapse rate was more than double (6.6%) in Kahaloo compared to Fulbari thana (3%). The rate was found to be highest among those who completed treatment for more than two years. Ten out of 18 relapse cases were identified by the TB control programme of WHDP. All the relapse cases were previously treated with anti-TB drugs for more than two months before the initiation of BRAC treatment Routine sputum examination for cured patients with complains of cough might be a strategy for identification of an relapse cases on time.